Research on Curriculum Reform and Practice of Power System in Application-Oriented Colleges - Fei Hu, Xisheng Zhan, Hongliang Gao (Forest Chemicals Review, 1970)
Aiming at the problems existing in the learning of power system analysis course of electrical engineering and automation specialty of application-oriented undergraduate, this paper deeply analyzes the ideas and methods of studying content reform and reflects the characteristics of the combination of theory and practice of application-oriented undergraduate. TO cultivate senior technical talents in electrical engineering, engineering application is integrated into the theoretical and practical learning of power system courses. Combined with the three power system professional courses of power system relay protection principle, power system automation, and power plant electrical part, according to the industry certification standards, optimize the classroom learning and practical learning mode, integrate and optimize the curriculum resources, realize the repetition and redundancy of learning contents of different courses, build an application-oriented learning mode of taking engineering application as the goal and paying equal attention to theory and practice, and strengthen computer-aided learning, Make full use of learning resources such as superstar wisdom classroom and rain classroom to enrich learning means. This study has important practical value and guiding significance for improving learning quality, improving pupils' professional ability, and cultivating technical talents to meet the needs of the power industry and enterprises.